2006
DOI: 10.1074/jbc.m512636200
|View full text |Cite
|
Sign up to set email alerts
|

Partnership of PGC-1α and HNF4α in the Regulation of Lipoprotein Metabolism

Abstract: Peroxisome proliferator-activated receptor ␥ coactivator-1␣ (PGC-1␣) is a transcriptional coactivator involved in several aspects of energy metabolism. It is induced or activated under different stimuli in a highly tissue-specific manner and subsequently partners with certain transcription factors in those tissues to execute various biological programs. In the fasted liver, PGC-1␣ is induced and interacts with hepatocyte nuclear factor 4␣ (HNF4␣) and other transcription factors to activate gluconeogenesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 54 publications
5
73
2
Order By: Relevance
“…PPAR ␥ coactivator-1 ␣ (PGC1 ␣ ) did not further activate the 5.9 kb Apoa4-luciferase reporter, despite it being known as a coactivator of HNF-4 ␣ ( 16, 25 ). HNF-4 ␣ failed to activate the 0.9 kb Apoa4-luciferase reporter, consistent with the requirement for apoCIII enhancer in HNF-4 ␣ -mediated apoA-IV activation ( 25 ). CREBH(N) cotransfection dramatically increased the luciferase activity of both 5.9 kb Apoa4-luciferase and 0.9 kb Apoa4-luciferase reporters by more than 1,000-fold ( Fig.…”
Section: Identifi Cation Of Crebh Recognition Sites On the Apoa4 Prommentioning
confidence: 61%
See 1 more Smart Citation
“…PPAR ␥ coactivator-1 ␣ (PGC1 ␣ ) did not further activate the 5.9 kb Apoa4-luciferase reporter, despite it being known as a coactivator of HNF-4 ␣ ( 16, 25 ). HNF-4 ␣ failed to activate the 0.9 kb Apoa4-luciferase reporter, consistent with the requirement for apoCIII enhancer in HNF-4 ␣ -mediated apoA-IV activation ( 25 ). CREBH(N) cotransfection dramatically increased the luciferase activity of both 5.9 kb Apoa4-luciferase and 0.9 kb Apoa4-luciferase reporters by more than 1,000-fold ( Fig.…”
Section: Identifi Cation Of Crebh Recognition Sites On the Apoa4 Prommentioning
confidence: 61%
“…2A ). Earlier studies demonstrated that nuclear hormone receptors such as HNF-4 ␣ and estrogen receptor ␣ (ERR ␣ ) activate apoA-IV transcription through the apoC-III enhancer, which is located near the Apoc3 gene ( 16,(23)(24)(25)(26). To investigate the roles of different transcription factors in Apoa4 transcription, luciferase reporter constructs containing 5.9 kb or 0.9 kb fragments of Apoa4 promoter were generated.…”
Section: Crebh Is the Major Transcription Factor Activating Apoa4 Tramentioning
confidence: 99%
“…PGC-1␣ is a central regulator of hepatic gluconeogenesis and induces the enzymes PEPCK and G-6-Pase via coactivation of FOXO1, HNF4␣, and the glucocorticoid receptor (43)(44)(45)(46). Reduced mRNA expression of PGC-1␣ was confirmed by qRT-PCR in fed and fasted mice (Fig.…”
Section: Pgc-1␣ Expression and Activity Are Suppressed-pgc-1␣mentioning
confidence: 71%
“…Remarkably, SIRT1 protein levels were also reduced, and Gcn5 transcripts were increased concomitantly. PGC-1␣ is a key driving factor of gluconeogenesis by coactivating FOXO1, HNF4␣ and the glucocorticoid receptor (43)(44)(45)(46). We showed that reduced PGC-1␣ activity may contribute to impaired gluconeogenesis in L-Pex5 Ϫ/Ϫ mice.…”
Section: L-pex5mentioning
confidence: 90%
“…HNF-4α is an important transcription factor in glucose and lipid metabolism in the liver and forms a complex with PGC-1α 31,32) . Levels of the HNF-4α/PGC-1α complex are increased in the liver of CR animals, and putative HNF-4RE-containing genes are up-regulated in pro-longevity contexts 4) .…”
Section: Possible Roles Of Hnf-4α In Metabolic Adaptation Of Crmentioning
confidence: 99%